UHPC jacket retrofitting of reinforced concrete bridge piers with low flexural reinforcement ratios: experimental investigation and three-dimensional finite element modeling. Issue 10 (3rd October 2021) - Tong, Teng; Wang, Jingquan; Lei, Haipeng; Liu, Zhao
Abstract: Many 'as-built' reinforced concrete (RC) bridge piers are suffering from insufficient flexural rebars in China. A novel retrofitting technique was proposed to enhance their seismic-resistant capacities, by enclosing the plastic hinge zone with the ultra-high performance concrete (UHPC) jacket. Three RC piers were loaded cyclically, with two of them retrofitted with the UHPC jackets of 400 and 850 mm height, respectively. The test validated the effectiveness of the UHPC jacket in enhancing a RC pier's lateral strength, self-centering capacity, energy dissipation capacity, etc. In addition, a three-dimensional (3D) continuum-based finite element (FE) framework is developed for the simulation of the UHPC jacket-retrofitted piers' behavior. The robust 3D FE model integrates the softened damage-plasticity (SDP) concrete model, Menegotto-Pinto steel model, and bond-slip behavior between concrete and reinforcements. Furthermore, the effectiveness of concrete damage plasticity model is also investigated, which is widely accepted and embedded in ABAQUS software. Equipped with viscous regularization, the FE model overcomes the convergence difficulty brought about by the material softening behavior, which enables the adoption of implicit incremental-iterative Newton-Raphson algorithm.